Precautionary Logic and Ignorance Interval Transfer Mediated Inference - Jan A. Bergstra (Scientific Annals of Computer Science)
A relatively formal framework for the description of application of the precautionary principle is described, which we consider to provide a basic setup for precautionary logic, that is reasoning patterns making use of said precautionary principle. Probability is understood as subjective probability in the tradition requiring exact figures for subjective probabilities. Besides probability we need various related concepts, notably: proposition, proposition space, truth, falsity, certainty, uncertainty, ignorance, hazard, harm, and risk. We adopt a fairly simple and coherent picture of these notions. We suggest that precautionary logic involves the transfer of quantified ignorance in the form of an ignorance interval.